2012
DOI: 10.1159/000338644
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Recurrence after Surgical Management of Urothelial Carcinoma of the Upper Urinary Tract

Abstract: Objectives: To elucidate clinicopathological risk factors for intravesical recurrence (IVR) in patients undergoing nephroureterectomy for upper urinary tract urothelial carcinoma (UUT-UC). Methods: We identified a study population of 151 consecutive patients without previous or concurrent bladder cancer who underwent nephroureterectomy for UUT-UC. IVR was assessed in relation to tumor location, size, and multifocality, operation modality and time, stage, grade, lymphovascular invasion, regional lymph node meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…In fact, a previous history of bladder cancer is present in 10–20% of patients with UTUC, and 8.5–13% of patients with UTUC have synchronous bladder cancer according to previous reports . Even in patients with no history of bladder cancer, the onset (recurrence) of bladder cancer is common after surgical treatment of UTUC, occurring in 15–50% of cases mostly within 2 years after surgery . Therefore, screening of the entire urinary tract is necessary when UTUC or bladder cancer is diagnosed.…”
Section: Epidemiologymentioning
confidence: 99%
“…In fact, a previous history of bladder cancer is present in 10–20% of patients with UTUC, and 8.5–13% of patients with UTUC have synchronous bladder cancer according to previous reports . Even in patients with no history of bladder cancer, the onset (recurrence) of bladder cancer is common after surgical treatment of UTUC, occurring in 15–50% of cases mostly within 2 years after surgery . Therefore, screening of the entire urinary tract is necessary when UTUC or bladder cancer is diagnosed.…”
Section: Epidemiologymentioning
confidence: 99%
“…Kang et al [9] and Hirano et al [10] reported that tumor multiplicity was the only independent risk factor for bladder recurrence in a multivariate analysis. Matsui et al [6], Terakawa et al [7], and Hisataki et al [12] also reported that tumor multiplicity was one of the independent risk factors for bladder recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors such as tumor configuration [8], tumor multiplicity [6,7,9,10], tumor stage [6,7,11,12], tumor grade [5,13], tumor location [5,14,15], patient gender [8,16,17], postoperative adjuvant systemic chemotherapy [16,18], and preoperative voided urine cytology [15,19] have been proposed, but the results remain controversial and no reliable conclusions could be drawn to aid surveillance strategies. Therefore, a clear knowledge of potential predictive factors for bladder recurrence in UUT-UC would allow better prognostic evaluation and aid surveillance strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Complete ureterectomy with removal of bladder cuff, previously resected endoscopically, should be considered the treatment of choice, similarly to TCC of the lower ureter [1]. Follow-up with cystoscopy should adhere to the same principles as for upper tract tumours post nephroureterectomy, as tumour multifocality has been shown to be a positive predictor for intravesical recurrence, especially during the first 2 years after treatment [20]. …”
Section: Discussionmentioning
confidence: 99%